PROBABLE CAUSE IN THE LOCAL TAX AND LEVY CRIMINAL - Leo B. Barus (Scientia Integritas Utama, 2022)
Criminal provisions for local or regional taxes and levies, as regulated in Article 181 and Article 183 of Law Number 1 of 2022 concerning Financial Relations between the Central Government and Local Governments, can create challenges for local taxes and levies and the potential for pre-trial. Based on juridical studies, two main conclusions are drawn: primary legal materials, secondary legal materials, and tertiary legal materials. First, the criminal provisions of Law Number 1 of 2022 do not provide legal certainty, considering that there is no lex specialist for investigators in the field of local taxation and levies in interpreting sufficient probable cause. Second, it is necessary to renew the criminal provisions in Law Number 1 of 2022 as the lex specialist of criminal law, including formulations of definitions, parameters, and standards of sufficient probable cause. It is recommended that the renewal of the criminal provisions of local taxes and levies contain normative provisions regarding adequate probable cause.